PENDAMPINGAN COMPETITIVE ADVANTAGE COST DAN COMPETITIVE ADVANTAGE DIFERENSIASI PADA INDUSTRI KAPUR GAMPING DI KECAMATAN PLUMPANG KABUPATEN TUBAN - Sutrisno; Moehadi; Hadi Susilo, Joko; Anggraini, Monica; Putri Amalia, Resa; Alfiyana, Siti (Universitas Kadiri, 2024)
Mentoring activities in the Cost Competitive Advantage and Differentiation Competitive Advantage strategies in the lime industry in Plumpang District, Tuban Regency aim to improve the company's competitiveness in the local market. This mentoring is focused on two main strategies, namely first, Cost Competitive Advantage which includes optimizing the production process with efficient technology, better raw material management, and controlling operational costs to reduce production costs. Second, Differentiation Competitive Advantage which is focused on product innovation, improving lime quality, product variations, and developing customer service programs and social responsibility to strengthen brand image. The implementation of this strategy is expected to improve the company's competitiveness and support sustainable growth in the lime industry.